PENGELOLAAN DANA DESA (ADD) (STUDI KASUS DI DESA JAHAB KECAMATAN TENGGARONG KABUPATEN KUTAI KARTANEGARA) - FETTY DESY KRISTIANTI PALADA; YUNUS TETE KONDE; AGUS SETIAWATI (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
The purpose of this study was to determine the accountability of the implementation of the Village Fund Allocation (ADD), and the factors that affect accountability for implementing the Village Fund Allocation (ADD) in the village Jahab Tenggarong District Kutai regency Fiscal Year 2015 is in conformity with the provisions applicable. Based on the survey results revealed Value Village Fund Allocation (ADD) received amounted Rp497.171.500,00 Jahab village in Fiscal Year 2015, consisting of direct expenditure (70%) and Indirect Expenditures (30%). With the value of Pos direct expenditure allocated 70% of the total Village Allocation Fund (ADD) in 2015 amounted to Rp349.997.000,00 and from the Post Indirect Expenditures allocated 30% of the total Village Allocation Fund (ADD) in 2015 amounted to Rp147. 174,500.00, meaning that the budget heading for development that is physically smaller than non-physical development allocated Rp147.174.500,00 (30%). Factors that affect the management of the Village Fund Allocation (ADD) in the village Jahab Tengarong District of Kutai regency Fiscal Year 2015 is the form factor inhibiting and supporting factors. Inhibiting factor consists of HR village officials are still low and still the complexity of the bureaucratic management of the Village Fund Allocation (ADD) of the district, especially in the liquefaction process. While supporting factors, which still support the community in development activities through self-help and mutual cooperation and their commitment Kutai District Government in strengthening the financial aspects of the village both in quantity and quality.Keywords: Village Fund Allocation (ADD)